Ratchet effects in currency substitution: An application to Nigeria - Sani Bawa; Babatunde S. Omotosho; Sani I. Doguwa (CBN Journal of Applied Statistics, 2015)
This study examines the persistence of currency substitution in Nigeria by applying the Bounds testing approach to cointegration and including a ratchet variable in the estimated Autoregressive Distributed Lag (ARDL) model. Empirical results show that factors such as exchange rate risks, expected exchange rate depreciation, exchange rate spread, inflation expectations as well as the ratchet variables are significant determinants of currency substitution in Nigeria, with the ratchet variables having overarching influence in the long run. This indicates that currency substitution is persistent in Nigeria and may portend negative implications for the stability of the money demand function as well as the effectiveness of monetary policy. Among others, the study recommends strong and sustained monetary policy intervention towards encouraging deposit holders and other economic agents to switch their currency portfolio back to Naira.
Keywords: C22; E41; E51; 330; Currency Substitution; Ratchet Effect; Cointegration; Monetary Policy; ARDL Model